Oxford dictionary of idioms - Ayto, John (Oxford quick reference., 2020)
What is it to 'cock a snook', where is the land of Nod, and who was first to go the extra mile? Find the answers to these questions (and many more!) in the new edition of the Oxford Dictionary of Idioms. This dictionary uncovers the meanings of myriad phrases and sayings that are used daily in the English language, encompassing more than 10,000 figurative expressions, similes, sayings, and proverbs. More than 400 idioms have been added to this new edition, and comprise recently coined and common sayings alike. New additions include 'back of the net', 'drag and drop', 'go it alone', 'how come?', 'if you ask me', 'make your skin crawl', and 'woe betide'. Illustrative quotations sourced from the Oxford corpora give contextual examples of the idioms and their standard usage, and many entries include background information on the origins of the idiom in question. An updated thematic index makes for easy navigation, and anyone who is interested in the origins and diversity of English vernacular will have hours of fun browsing this fascinating dictionary.